Circulating Mesencephalic Astrocyte-Derived Neurotrophic Factor Negatively Correlates With Atrial Apoptosis in Human Chronic Atrial Fibrillation. Issue 2 (February 2020) - Wang, Changhui; Yu, Shujun; Bao, Qin; Qiang, Weimin; Wu, Chaoran; Zhang, Chengxin; Jiang, Yan; Cai, Yongping; Huang, Dake; Chen, Ying; Hou, Chao; Wang, Dong
Abstract : Abstract: Atrial apoptosis has been found to be majorly involved in the pathogenesis of human atrial fibrillation (AF). Mesencephalic astrocyte-derived neurotrophic factor exerts an antiapoptotic effect for multiple cell types. However, the correlation between MANF and atrial apoptosis in AF is still undefined. In this study, 59 patients with valvular or congenital heart disease were divided into 2 groups: AF group and sinus rhythm (SR) group. We found that the apoptotic atrial myocytes in the right atrial appendage tissues of the AF group were significantly more than those of the SR group, whereas mRNA and protein levels of MANF in the AF group were significantly down-regulated compared with those in the SR group. The serum MANF in patients with AF was markedly lower than that in patients with SR, which was inversely correlated with atrial apoptosis in patients with AF. In addition, the AF group had the greater inflammation and endoplasmic reticulum stress compared with the SR group. These findings suggest that MANF downregulation may lead to more atrial apoptosis in human chronic AF, indicating MANF as a potential therapeutic agent in AF treatment.